The Effect of Honey in Second Degree Burn Healing on Wistar Rats (Overview of Angiogenesis and the Number of Fibroblasts) - Almaz, Ayyasi Izaz; Purnawati, Ratna Dama; Istiadi, Hermawan; susilaningsih, Neni (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Burn therapy is generally done using a burn ointment. However, honey can also be used as an alternative treatment for burns. Honey contains active flavonoid as an antioxidant and hydrogen peroxide which can stimulate fibroblasts proliferation also angiogenesis on burn healing phase.Objective: to determine the effect of honey in second degree burn healing from angiogenesis and the number of fibroblasts on Wistar rats. Methods: This research used a posttest only controlled group design on 15 rats with random selection and divided into 3 groups: H-G was given honey, B-G was given BioplacentonÂ®, N-G without any treatment after burn was induced. Rats were given a second degree burn in a size of 2 cm x 2cm on the back area and were treated twice a day for 14 days. Burn healing was measured by calculating the observation results of microscopic VEGF expression, the number of neovascularization, and the number of fibroblasts. Hypothesis analysis used Annova post hoc LSD and Mann-Whitney.Results: The highest mean in VEGF expression and the number of neovascularization was obtained from group B-G followed by group H-G and group N-G. Significant differences in the number of neovascularization between group B-G with group N-G, p<0.05.Conclusion: Honey can provide a healing effect on the second degree of burns in Wistar rats in terms of the number of neovascularization as well as BioplacentonÂ®